Sustainable transport infrastructure: Road asset management in the CAREC region - Dildar Zakir; Ian Greenwood; Ayoob Ayoobi (Asian Development Bank Institute (ADBI), 2024)
The Central Asia Regional Economic Cooperation (CAREC) region has historically been an important route for global trade - connecting Asia to Europe (and vice versa) and beyond through the ancient Silk Road before the evolution of maritime trade and commerce in the 1500s. The Asian Development Bank initiated the subregion development program, CAREC, in 2006 with the aim of reviving the region's commerce and trade significance by investing in six CAREC corridors. In 2013, the People's Republic of China (PRC) launched the Belt and Road Initiative to further accelerate efforts on this front. In general, over the past two decades a lot of investment has been made in reviving the ancient Silk Road. Since 2010, the Asian Development Bank (ADB) has been putting significant effort into upgrading and building CAREC corridors, which run through the whole region. These corridors enhance inter- and intraregional connectivity and consequently promote regional economic cooperation and cross-border trade. While further efforts and resources need to be optimized for upgrading and building the corridors, special attention must be paid to looking after these corridors in terms of sustainable asset management. This paper investigates road asset management (RAM) practices within the CAREC nations through which the CAREC corridors pass, with the objectives of understanding (i) what the current status of RAM is, (ii) the importance of RAM to the CAREC corridors, and (iii) the role of RAM in addressing climate change, and also (iv) identifying policies for RAM implementation. The paper draws on data collected through RAM maturity assessments for 17 primary aspects of RAM practice that were completed via a self-assessment methodology, but with subsequent validation completed in four CAREC countries. The findings indicate that while the best practice within the region for any individual aspect of RAM is of an acceptable level, there is significant variation in results both between countries and between aspects of RAM within a given country. Finally, the paper has used the findings to develop a range of policies that could be used to create a more sustainable and resilient road network for the region - thereby enabling the benefits envisioned from the investments in the corridors to be realized.
Keywords: R42; O18; 330; road asset management; maturity assessment; sustainable transport; CAREC Institute